Method for selectively extracting lithium from electrolytic aluminum waste
Through high-temperature calcination and a two-stage leaching process that controls the leaching pH value, combined with two-stage impurity removal and sodium carbonate precipitation, the problem of efficient lithium extraction in electrolytic aluminum waste is solved, and high recovery rate and low-cost battery-grade lithium carbonate preparation is achieved.
Patent Information
- Application Number
- CN202411751314.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art cannot efficiently extract lithium from electrolytic aluminum scrap, and there are problems such as long process, large energy consumption, and unfriendly environment. Especially, electrolytic aluminum scrap with low lithium content and high carbon content is difficult to handle, and the lithium recovery rate is low.
Carbon is removed by high-temperature calcination, and the leaching pH value is controlled to be between 3.0 and 4.0 for two-stage leaching. Combined with the two-stage impurity removal process, oxalic acid is used as the calcium removal agent, and finally, battery-grade lithium carbonate is prepared by sodium carbonate precipitation and CO2 reaction.
It significantly improves the recovery rate and concentration of lithium, reduces the processing cost and difficulty, and achieves efficient extraction of battery-grade lithium carbonate, reduces environmental pollution and simplifies the operation process.
Smart Images

Figure CN119800103A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of extraction and utilization of lithium-containing waste from electrolytic aluminum, and in particular to a method for selectively extracting lithium from electrolytic aluminum waste. Background Art
[0002] In recent years, the new energy industry has developed rapidly, and the demand for lithium in the field of lithium-ion batteries and energy storage has continued to grow. Many domestic companies have deployed lithium resource extraction technology development and are committed to the production of lithium carbonate to meet the growing demand for lithium. At present, my country's productivity level continues to develop, people's living standards are gradually improving, and the development of industries such as automobiles has driven the continuous growth of the electrolytic aluminum industry. The output of electrolytic aluminum waste slag continues to increase. Electrolytic aluminum waste slag contains a certain amount of lithium, but it contains a large amount of aluminum. Extracting and utilizing valuable metals such as lithium and aluminum can save a lot of lithium and aluminum resources. This material extraction and utilization technology has been rapidly developed and developed in recent years.
[0003] For example, the Chinese invention with application number 201310147358.2 discloses a method for simultaneously recovering cryolite and carbon powder from electrolytic aluminum waste slag. The invention crushes the electrolytic aluminum waste slag into powder, mixes it into a slurry prepared by kerosene, ethanol and water, adds the slurry into an aqueous solution containing sodium silicate and sodium aluminate, and separates it into three layers, upper, middle and lower, after stirring and standing. The upper layer is centrifuged, dehydrated, washed and dried to obtain carbon powder, the lower layer is precipitated, filtered, washed and dried to obtain cryolite, and the middle layer is an aqueous solution containing sodium silicate and sodium aluminate. The invention will cause environmental pressure due to the addition of organic matter such as kerosene and ethanol, and only recovers cryolite and carbon powder from the electrolytic aluminum waste slag, and lithium is not reasonably utilized.
[0004] The Chinese invention with application number 202310704041.8 discloses a process for improving the lithium leaching rate in the difficult-to-leach aluminum electrolytic waste slag, which comprises the following steps: preparing 10L of 5% aluminum chloride solution, adding 10g of waste slag to every 100ml of aluminum chloride solution, adding 1kg of waste slag to control the end point pH value to 3, leaching for 2 hours at room temperature, filtering and washing the filter residue, the filter residue is mainly impurities such as carbon, and the filtrate enters the impurity removal enrichment and purification process. The present invention uses an aluminum salt solution to dissolve the lithium sodium cryolite in the difficult-to-leach aluminum electrolytic waste slag, so that the lithium therein can be converted into lithium chloride or lithium sulfate, etc., thereby improving the lithium leaching rate in the difficult-to-leach aluminum electrolytic waste slag, and effectively solving the problem of low lithium leaching rate and environmental unfriendly in the existing recovery process. The method uses aluminum chloride as a dissolving medium, and the leaching solution contains extremely high aluminum. Although the lithium leaching rate is high, the low lithium concentration and high aluminum content in the leaching solution affect the recovery of lithium.
[0005] The Chinese invention with publication number CN116005006A discloses a method for extracting lithium from waste aluminum slag, wherein the waste aluminum slag is dried, ground and impurities removed, and calcium carbonate, water and concentrated sulfuric acid are added to react at 80-100°C to separate the leaching solution; calcium oxide is added, pH is adjusted to 10-11, and the filtrate is separated; the filtrate is cooled and crystallized, and concentrated after separation to obtain a concentrated solution; sodium carbonate and flocculant are added to the concentrated solution, stirred and separated to obtain a lithium sulfate solution; sodium carbonate solution is added to the lithium sulfate solution, and then separated to obtain crude lithium carbonate and mother liquor, and the mother liquor and the filtrate are cooled and crystallized together, and concentrated after separation to obtain the concentrated solution; the crude lithium carbonate obtained is washed, dried and crushed to obtain battery-grade lithium carbonate. The purity of the obtained product meets the industry standard for battery-grade lithium carbonate, the reaction conditions are mild, there is no hydrogen fluoride waste gas, the lithium leaching rate is high, the equipment requirements are low, the energy consumption is low, and it is suitable for industrial production. This method uses calcium-containing compounds to remove impurities and adjust the pH value. The amount of calcium sulfate slag is large, and the aluminum content in the material is high. The impurity removal produces a large amount of waste slag, resulting in a reduced lithium recovery rate. The process has no calcium removal process, which will cause pipeline crystallization and a low yield of battery-grade lithium carbonate.
[0006] For electrolytic aluminum waste with a lithium content of about 1% and high sodium, aluminum and carbon content, the amount of sodium sulfate crystallization during the lithium extraction process is large, and the precipitation and filtration properties are poor, which affects the total recovery rate of lithium. This type of material contains about 50% carbon. The carbon content of this material is relatively high, accounting for about 50%. It is insoluble in the leaching process. As a leaching slag, the loss of lithium in the slag increases, and the subsequent processing is labor-intensive. The existing technology cannot solve the above problems and efficiently extract lithium. Summary of the invention
[0007] Therefore, in order to solve the problems of long process and high energy consumption in the prior art, a method for selectively extracting lithium from electrolytic aluminum waste is proposed. This method selectively extracts lithium from waste aluminum slag by controlling the leaching conditions, while limiting the leaching of impurities such as aluminum and iron in the slag, and obtains high-quality lithium sulfate for further preparation of lithium carbonate. The specific scheme is as follows:
[0008] A method for selectively extracting lithium from electrolytic aluminum waste, comprising the following steps:
[0009] Step 1: crushing the electrolytic aluminum waste with a carbon content of more than 45% and an aluminum content of more than 10 times the lithium content;
[0010] Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, and then cooling and fine grinding to 60-200 mesh to obtain a decarbonized material;
[0011] Step 3: subjecting the decarbonized material to two-stage leaching, wherein the pH value of the first-stage leaching is controlled at 3.5-4.0, and filtering after the first-stage leaching to obtain a first-stage leaching liquid and a first-stage leaching residue; subjecting the first-stage leaching residue to a second-stage leaching, wherein the pH value of the second-stage leaching is controlled at 3.0-3.5, to obtain a second-stage leaching liquid and a second-stage leaching residue, and returning the second-stage leaching liquid to the first-stage leaching process;
[0012] Step 4: performing two-stage impurity removal, wherein the first-stage impurity removal process is: adding an oxidant to the first-stage leaching solution, then adding alkali to adjust the pH value to 4.5-5.0, and filtering to obtain a filtrate and a filter residue; the second-stage impurity removal process is: adding a decalcifying agent to the filtrate, then adding alkali to adjust the pH value to 12.0-13.0, and filtering to obtain a lithium-containing filtrate and an impurity filter residue;
[0013] Step 5: The lithium-containing filtrate is heated and concentrated, and then subjected to a freezing crystallization step to obtain a denitrified liquid;
[0014] Step 6: adding sodium carbonate solution to the denitrified liquid under heating conditions, precipitating and filtering to obtain crude lithium carbonate;
[0015] Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it precisely to obtain a lithium carbonate solution. Heat, crystallize, filter, wash and dry to obtain battery-grade lithium carbonate.
[0016] Furthermore, the composition and mass proportion of the electrolytic aluminum waste in step 1 are: lithium 1%-1.2%, aluminum 12.5-12.9%, sodium 12.6-13.0%, iron 1.0-1.1%, calcium 2.1-2.2%, magnesium 0.24-0.26%, silicon <0.1%, fluorine 13.5-14.0%, sulfur 0.10-0.11%, carbon >45%, and the rest is water.
[0017] Furthermore, the size of the electrolytic aluminum waste after crushing in step 1 is 1-10 cm.
[0018] Furthermore, in the leaching process in step 3, the leaching agent is 98% sulfuric acid by mass, the leaching temperature is 60-90°C, the leaching time is 1-5h, the slurry liquid-solid ratio of water to carbon removal material in the first leaching is 3-5:1, the slurry liquid-solid ratio of the second leaching is 2-5:1, and the second leaching residue is washed and the washed liquid is returned to the first leaching.
[0019] Furthermore, in step 4, the oxidant in the first impurity removal process is hydrogen peroxide, sodium chlorate, sodium hypochlorite, chlorine, air or oxygen, the impurity removal temperature is 55-70°C, the alkali is a sodium hydroxide solution with a mass concentration of 5-20%, and the reaction time is 1-5h; the reaction time in the second impurity removal process is 1-5h, the decalcifying agent is oxalic acid, and the amount of the decalcifying agent added is 0.05%-0.1% of the electrolytic aluminum waste.
[0020] Furthermore, the temperature of the freezing crystallization in step 5 is -10°C to 10°C.
[0021] Furthermore, the heating temperature in step 6 is 90-100°C.
[0022] Furthermore, in step 7, the mass ratio of pure water to crude lithium carbonate is 9-10:1, and the pressure of the introduced CO2 gas is 0.1-0.2 MPa.
[0023] Furthermore, the temperature of the heating crystallization in step 7 is 90-100°C.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] (1) The electrolytic aluminum waste of the present invention is first calcined at above 550°C to remove most of the carbon therein, so that the lithium extraction processing capacity can be increased by almost one-fold, and the concentration of the lithium solution can be increased by about one-fold, which greatly reduces the processing difficulty and cost and improves the lithium recovery rate and processing efficiency.
[0026] (2) The present invention controls the pH value of the leaching process to 3.0-4.0 and performs the process in two stages. Within the pH value range, the lithium in the electrolytic aluminum waste is dissolved as fully as possible, while most of the aluminum, iron, sodium, fluorine, etc. are not dissolved and remain in the leaching residue, reducing the amount of leaching acid used and greatly reducing the amount of alkali used during impurity removal. At the same time, since the aluminum content in the material is very high, the leaching of aluminum is inhibited by controlling the acidity of the leaching solution, and the large amount of lithium loss caused by the adsorption of lithium by aluminum hydroxide in a colloidal state during impurity removal is reduced. The slag filtering performance is good, and the reduced amount of alkali used greatly reduces the sodium content in the lithium solution after impurity removal. Only one denitration is required to meet the requirements, reducing the burden of each process, and reducing the cost of lithium extraction and the difficulty of operation. At the same time, two-stage atmospheric pressure leaching is adopted, and the leaching temperature is 60-90°C to improve the lithium leaching rate, and the lithium leaching rate can reach more than 95%. The leaching conditions are mild, the processing cost is low, and it is easy to operate.
[0027] (3) The lithium leaching solution of the present invention is subjected to two-stage impurity removal, wherein the first stage removes iron and aluminum impurities, and the second stage removes other impurities such as iron, manganese, and calcium. The main products of the two stages of impurity removal are different and are processed separately. In the two-stage impurity removal process, oxalic acid is used as a decalcifying agent instead of conventional ion exchange resin, which can avoid the generation of excessive wastewater and the problem of easy scaling of ion exchange resin in sulfuric acid system, so that calcium can be removed efficiently and the system operates smoothly.
[0028] The method of the invention can effectively extract lithium from electrolytic aluminum waste to prepare battery-grade lithium carbonate. The main component of the leached slag is cryolite, which can be utilized with good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0030] Figure 1 The process flow chart of the present invention is shown. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] A method for selectively extracting lithium from electrolytic aluminum waste, comprising the following steps:
[0033] Step 1: Crushing the electrolytic aluminum waste with a carbon content of more than 45% and an aluminum content of more than 10 times the lithium content. The size of the crushed electrolytic aluminum waste is 1-10cm; the composition and mass proportion of the electrolytic aluminum waste are as follows: lithium 1%-1.2%, aluminum 12.5-12.9%, sodium 12.6-13.0%, iron 1.0-1.1%, calcium 2.1-2.2%, magnesium 0.24-0.26%, silicon <0.1%, fluorine 13.5-14.0%, sulfur 0.10-0.11%, carbon>45%, and the rest is water. .
[0034] Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, and then cooling and fine grinding to 60-200 mesh to obtain a decarbonized material;
[0035] Step 3: subjecting the decarbonizing material to two-stage leaching, wherein the pH value of the first stage leaching is controlled at 3.5-4.0, and filtering after the first stage leaching to obtain a first stage leaching liquid and a first stage leaching residue; subjecting the first stage leaching residue to two-stage leaching, wherein the pH value of the second stage leaching is controlled at 3.0-3.5, to obtain a second stage leaching liquid and a second stage leaching residue, and returning the second stage leaching liquid to the first stage leaching process; during the leaching process, the slurry liquid-solid ratio of water to the decarbonizing material is 3-5:1, the leaching agent is 98% sulfuric acid, the leaching temperature is 60-90°C, and the leaching time is 1-5h; the liquid-solid ratio of the second stage leaching is 2-5:1, the leaching time is 1-5h, and after washing the second stage leaching residue, the washed liquid is returned to the first stage leaching.
[0036] 2LiF+H2SO4→Li2SO4+2HF↑
[0037] 2Na3AlF6+6H2SO4→3Na2SO4+Al2(SO4)3+6HF↑
[0038] Fe+H2SO4→FeSO4+H2↑
[0039] Step 4: performing two-stage impurity removal, wherein the first stage impurity removal process is: adding an oxidant to the first stage leaching solution, and then adding alkali to adjust the pH value to 4.5-5.0, filtering to obtain a filtrate and a filter residue; the oxidant in the first stage impurity removal process is hydrogen peroxide, sodium chlorate, sodium hypochlorite, chlorine, air or oxygen, the impurity removal temperature is 55-70° C., the alkali is a sodium hydroxide solution with a mass concentration of 5-20%, and the reaction time is 1-5 hours;
[0040] 2FeSO4+H2SO4+H2O2→Fe2(SO4)3+2H2O (chemical equation with hydrogen peroxide as oxidant)
[0041] Al2(SO4)3+6NaOH→3Na2SO4+2Al(OH)3↓
[0042] Fe2(SO4)3+6NaOH→3Na2SO4+2Fe(OH)3↓
[0043] The second stage impurity removal process is: add decalcifying agent oxalic acid to the filtrate, then add alkali to adjust the pH value to 12.0-13.0, and filter to obtain lithium-containing filtrate and impurity filter residue; the reaction time in the second stage impurity removal process is 1-5h, the decalcifying agent is, and the amount of decalcifying agent added is 0.05%-0.1% of the electrolytic aluminum waste.
[0044] Mn 2+ +2NaOH→2Na + +Mn(OH)2↓
[0045] H2C2O4+Ca 2+ →CaC2O4↓+2H +
[0046] Mg 2+ +2NaOH→2Na + +Mg(OH)2↓
[0047] Step 5: Heat and concentrate the lithium-containing filtrate, and then perform a freeze crystallization to obtain a denitrified liquid; the freeze crystallization temperature is -10°C-10°C to remove sodium sulfate.
[0048] Step 6: Add sodium carbonate solution to the denitrified liquid under heating conditions, and filter the precipitate to obtain crude lithium carbonate; the heating temperature is 90-100°C.
[0049] Li2SO4+Na2CO3→Li2CO3↓+2Na2SO4
[0050] Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it accurately to obtain a lithium carbonate solution. Heat it for crystallization, filter it, wash it, and dry it to obtain battery-grade lithium carbonate. The mass ratio of pure water to crude lithium carbonate is 9-10:1, the pressure of the CO2 gas introduced is 0.1-0.2MPa, and the temperature of heating crystallization is 90-100℃.
[0051] The specific embodiments are as follows:
[0052] The electrolytic aluminum scrap used in the following examples is in the form of hard blocks with a carbon content exceeding 50%. The main components of the material are shown in Table 1.
[0053] Table 1 Composition and content of electrolytic aluminum waste
[0054]
[0055] Example 1
[0056] (1) Take a certain amount of electrolytic aluminum waste and crush it into small pieces of about 5 cm using a crusher or manually.
[0057] (2) Weigh 4000 g of the sieved material, put it into a crucible, and place it in a calcining furnace at 700°C for 5 hours. Cool it to room temperature, take out the material and grind it through an 80-mesh sieve.
[0058] (3) The decarbonizing material and water are mixed and stirred evenly at a liquid-solid ratio of 5:1, 98% sulfuric acid is added, and the mixture is heated to 80°C for a first-stage leaching, sulfuric acid is added to adjust the pH value to 3.5, the leaching is carried out for 1 hour, and the first-stage leaching solution and the first-stage leaching residue are obtained. The first-stage leaching residue is slurried with sulfuric acid at a liquid-solid ratio of 3:1 and then subjected to a second leaching, the pH value at the leaching end point is 3.0, the leaching is carried out for 1 hour, and the second-stage leaching solution and the second-stage leaching residue are obtained. The second-stage leaching residue is washed twice, the first-stage leaching solution is subjected to subsequent treatment, and the washing water of the second-stage leaching solution and the second-stage leaching residue is combined for a first-stage leaching slurry or leaching; the leaching kettle is connected to an absorption device, and the absorption liquid is pure water to absorb the HF gas generated during the leaching process; the lithium leaching rate is 96.03%, the iron leaching rate is 33.55%, and the aluminum leaching rate is 2.08%.
[0059] (4) Impurity removal: The first-stage leachate is subjected to two-stage impurity removal. The first-stage impurity removal is as follows: 1.2 times the theoretical amount of hydrogen peroxide is added to the first-stage leachate, and then 5% sodium hydroxide is added to adjust the pH value to 4.5. The reaction temperature is maintained at 60° C. The reaction time is 4 hours. The filtrate and filter residue are obtained by filtration. The filter residue is slurried and washed twice. The filtrate is subjected to two-stage impurity removal. 2 g of decalcifying agent oxalic acid is added, and then 5% sodium hydroxide is added to adjust the pH value to 12.5. The reaction time is 3 hours. The lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored;
[0060] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and then the sodium sulfate is crystallized by freezing to obtain the denitrified liquid.
[0061] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 90°C to precipitate crude lithium carbonate.
[0062] (7) Add 10 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.1 MPa, and accurately filter after all the lithium carbonate is dissolved to obtain a lithium carbonate solution. Heat the lithium solution to a slightly boiling temperature (90-100°C) for crystallization, filter, wash, and dry to obtain battery-grade lithium carbonate.
[0063] Example 2
[0064] (1) Take a certain amount of electrolytic aluminum waste and crush it into small pieces of about 5 cm using a crusher or manually.
[0065] (2) 1000 g of the coarsely crushed material is placed in a crucible, which is then placed in a calcining furnace at a temperature of 1400° C. for 3 h. The material is finely ground and passed through a 200-mesh sieve for later use to obtain a decarbonized material.
[0066] (3) The carbon removal material and water were mixed and stirred evenly at a liquid-to-solid ratio of 3:1, 98% sulfuric acid was added, and the mixture was heated in a water bath at 70°C for a first leaching, sulfuric acid was added to adjust the pH value to 3.5, the mixture was leached for 3 hours, and the mixture was filtered after leaching to obtain a first leaching solution and a first leaching residue. The first leaching residue was slurried with sulfuric acid at a liquid-to-solid ratio of 3:1 and then subjected to a second leaching, the pH value at the leaching end point was 3.0, the mixture was leached for 3 hours, and the mixture was filtered after leaching to obtain a second leaching solution and a second leaching residue. The second leaching residue was washed twice, the first leaching solution was subjected to subsequent treatment, and the washing water of the second leaching solution and the second leaching residue was combined for a first leaching slurry or leaching; the lithium leaching rate was 96.25%, the iron leaching rate was 36.33%, and the aluminum leaching rate was 2.03%.
[0067] (4) Impurity removal: The first-stage leachate is subjected to two-stage impurity removal. The first-stage impurity removal is as follows: 1.1 times the theoretical amount of sodium chlorate is added to the first-stage leachate, and then 10% sodium hydroxide is added to adjust the pH value to 4.5. The reaction temperature is maintained at 70° C. The reaction time is 1 hour. The filtrate and filter residue are obtained by filtration. The filter residue is slurried and washed twice. The filtrate is subjected to two-stage impurity removal. 1 g of decalcifying agent oxalic acid is added, and then 10% sodium hydroxide is added to adjust the pH value to 12.0. The reaction time is 1 hour. The lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored;
[0068] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and then the sodium sulfate is crystallized by freezing to obtain the denitrified liquid.
[0069] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 95°C to precipitate crude lithium carbonate.
[0070] (7) Add 9 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.2 MPa. After all the lithium carbonate is dissolved, fine filtration is performed to obtain a lithium carbonate solution. The lithium solution is heated to a slightly boiling temperature (90-100°C) for crystallization, and filtered, washed, and dried to obtain battery-grade lithium carbonate.
[0071] Example 3
[0072] (1) Take a certain amount of electrolytic aluminum waste and crush it into small pieces of about 5 cm using a crusher or manually.
[0073] (2) 15 kg of the coarsely crushed material is placed in a crucible and placed in a calcining furnace at a calcination temperature of 1600° C. for 3 h. The material is finely ground and passed through a 60-mesh sieve for later use to obtain a decarbonized material.
[0074] (3) The carbon removal material and water were mixed and stirred evenly at a liquid-to-solid ratio of 3:1, 98% sulfuric acid was added, and the mixture was heated at 90°C in a water bath for a first leaching, sulfuric acid was added to adjust the pH value to 3.0, and the mixture was leached for 5 hours. After leaching, the mixture was filtered to obtain a first leaching solution and a first leaching residue. The first leaching residue was slurried with sulfuric acid at a liquid-to-solid ratio of 3:1 and subjected to a second leaching, the pH value at the leaching end point was 3.5, and the mixture was leached for 5 hours. After leaching, the mixture was filtered to obtain a second leaching solution and a second leaching residue. The second leaching residue was washed twice, the first leaching solution was subjected to subsequent treatment, and the washing water of the second leaching solution and the second leaching residue was combined for a first leaching slurry or leaching; the lithium leaching rate was 96.44%, the iron leaching rate was 34.56%, and the aluminum leaching rate was 2.05%.
[0075] (4) Impurity removal: The first-stage leachate is subjected to two-stage impurity removal. The first-stage impurity removal is as follows: oxygen is introduced into the first-stage leachate for 60 minutes, 20% sodium hydroxide is added to adjust the pH value to 4.5, the reaction temperature is maintained at 65° C., the reaction time is 5 hours, and the filtrate and filter residue are obtained by filtration. The filter residue is slurried and washed twice, and the filtrate is subjected to two-stage impurity removal. 10 g of decalcifying agent oxalic acid is added, and then 20% sodium hydroxide is added to adjust the pH value to 13.0. The reaction time is 5 hours, and the lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored;
[0076] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and then the sodium sulfate is crystallized by freezing to obtain the denitrified liquid.
[0077] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 98°C to precipitate crude lithium carbonate.
[0078] (7) Add 10 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.2 MPa, and then accurately filter after all the lithium carbonate is dissolved to obtain a lithium carbonate solution. The lithium solution is heated to a slightly boiling temperature (90-100°C) for crystallization, and filtered, washed, and dried to obtain battery-grade lithium carbonate.
[0079] Table 1 Composition of the final lithium carbonate product in the embodiment
[0080] Serial number <![CDATA[Li2CO3]]> Al Fe Na Ca Mg Mn Example 1 99.69 0.00077 0.00043 0.0221 0.0029 0.0009 0.00018 Example 2 99.71 0.00075 0.00051 0.0235 0.0030 0.0007 0.00021 Example 3 99.66 0.00063 0.00044 0.0233 0.0032 0.0008 0.00019
[0081] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. A method for selectively extracting lithium from electrolytic aluminum waste, characterized in that: The following steps are involved: Step 1: crushing the electrolytic aluminum waste with a carbon content of more than 45% and an aluminum content of more than 10 times the lithium content; Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, and then cooling and fine grinding to 60-200 mesh to obtain a decarbonized material; Step 3: subjecting the decarbonized material to two-stage sulfuric acid leaching, wherein the pH value of the first leaching is controlled at 3.5-4.0, and filtering after the first leaching to obtain a first leaching solution and a first leaching residue; subjecting the first leaching residue to a second-stage leaching, wherein the pH value of the second leaching is controlled at 3.0-3.5, to obtain a second-stage leaching solution and a second-stage leaching residue, and returning the second-stage leaching solution to the first leaching process; Step 4: performing two-stage impurity removal, wherein the first-stage impurity removal process is: adding an oxidant to the first-stage leaching solution, then adding alkali to adjust the pH value to 4.5-5.0, and filtering to obtain a filtrate and a filter residue; the second-stage impurity removal process is: adding a decalcifying agent to the filtrate, then adding alkali to adjust the pH value to 12.0-13.0, and filtering to obtain a lithium-containing filtrate and an impurity filter residue; Step 5: heating and concentrating the lithium-containing filtrate, and then freezing and crystallizing it to obtain a denitrified liquid; Step 6: adding sodium carbonate solution to the denitrified liquid under heating conditions, precipitating and filtering to obtain crude lithium carbonate; Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it precisely to obtain a lithium carbonate solution. Heat, crystallize, filter, wash and dry to obtain battery-grade lithium carbonate.
2. The method for selectively extracting lithium from electrolytic aluminum waste according to claim 1, characterized in that: The composition and mass proportion of the electrolytic aluminum waste in step 1 are: lithium 1%-1.2%, aluminum 12.5-12.9%, sodium 12.6-13.0%, iron 1.0-1.1%, calcium 2.1-2.2%, magnesium 0.24-0.26%, silicon <0.1%, fluorine 13.5-14.0%, sulfur 0.10-0.11%, carbon>45%, and the rest is water.
3. The method for selectively extracting lithium from electrolytic aluminum waste according to claim 1, characterized in that: The size of the electrolytic aluminum scrap after crushing in step 1 is 1-10 cm.
4. The method for selectively extracting lithium from electrolytic aluminum waste according to claim 1, characterized in that: In the leaching process in step 3, the leaching agent is 98% sulfuric acid by mass, the leaching temperature is 60-90° C., the leaching time is 1-5 hours, the slurry liquid-solid ratio of water to carbon removal material in the first leaching is 3-5:1, the slurry liquid-solid ratio of the second leaching is 2-5:1, and the second leaching residue is washed and the washed liquid is returned to the first leaching.
5. The method for selectively extracting lithium from electrolytic aluminum waste according to claim 1, characterized in that: In step 4, the oxidant in the first stage impurity removal process is hydrogen peroxide, sodium chlorate, sodium hypochlorite, chlorine, air or oxygen, the impurity removal temperature is 55-70°C, the alkali is a sodium hydroxide solution with a mass concentration of 5-20%, and the reaction time is 1-5h; the reaction time in the second stage impurity removal process is 1-5h, the decalcifying agent is oxalic acid, and the amount of the decalcifying agent added is 0.05%-0.1% of the electrolytic aluminum waste.
6. The method for selectively extracting lithium from electrolytic aluminum waste according to claim 1, characterized in that: The temperature of the freezing crystallization in step 5 is -10°C to 10°C.
7. The method for selectively extracting lithium from electrolytic aluminum waste according to claim 1, characterized in that: The heating temperature in step 6 is 90-100°C.
8. The method for selectively extracting lithium from electrolytic aluminum waste according to claim 1, characterized in that: In step 7, the mass ratio of pure water to crude lithium carbonate is 9-10:1, and the pressure of the introduced CO2 gas is 0.1-0.2MPa.
9. The method for selectively extracting lithium from electrolytic aluminum waste according to claim 1, characterized in that: The temperature of heating crystallization in step 7 is 90-100°C.
Citation Information
Patent Citations
Method for synchronously recycling cryolite and carbon powder from electrolytic aluminum waste residue
CN103193256B
Method for extracting lithium from electrolytic aluminum waste residues and application of method
CN116005006A
Process method for improving leaching rate of lithium in refractory aluminum electrolysis waste residues
CN116732347A
Cited By
Electrolyte high-pressure heat treatment lithium extraction and impurity removal method and application
CN121555776A
Method for extracting lithium and removing impurities from electrolyte by high-pressure heat treatment and application thereof
CN121555776B
Method for extracting lithium from solid waste of aluminum electrolysis cell
CN121874503A